SIGNIFICANCE OF KNOWLEDGE AND EXPANDED SEQUENCE: A CRIATIVE PROPOSAL TO WORK WITH LITERARY TEXTS - Batistella Bianchini, Luciane Guimaraes [UNESP]; Arruda, Renata Beloni de; Figliolo, Gustavo Javier (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2015)
One of the challenges in teaching Literature comes from the lack of interest of students about the subject. This may happen because several texts are explored out of any context, without the possibility of significance of knowledge by the student. We consider literary literacy as a possibility of teaching and learning literary works, since it is based in proposals that involve autonomous interpretations (inferences) from the student in the process of knowing. Our research is bibliographical and tends to analyze a proposal of expanded sequence as a working guide to Literature Teaching. For its application, there was chosen a literary work for students of high school interacting with texts of different genders. We concluded that the proposal may arouse interest of students due to the reflexive and gradually constructed procedure promoted as far as students are called upon an active relationship with many possibilities of knowledge of the work in question.
Keywords: Literary Literacy; Knowledge; Interest in Reading; Expanded Sequence